Idaho - Kent, Deborah (New York : Children's Press, 2010)
Takes readers on a tour of Idaho, describing the state's history, culture, land, economy, government, and sights, and including unique facts, color maps and photos, the state song, suggested activities, lists of famous people, cultural institutions, and annual events, and other resources.
Land -- First people -- Exploration and settlement -- Growth and change -- More modern times -- People -- Government -- Economy -- Travel guide.
Includes bibliographical references and index.
Keywords: Idaho -- Juvenile literature; Idaho